Es bueno para el esquiador esquiar -valokuvanäyttely - Ulkuniemi, Seija (Museo Ambiente Histórico Cubano, Casa de Velázquez, 2024)
I will take you on a trip to the Finnish winter landscape. Cool: in Lapland in winter the temperature is usually between two and thirty minus degrees Celsius. When it's a bit warmer, I often take long ski trips to the forest near my home village. In my village there is a lighted slope for fast skiing, because in Finland there is little daylight in winter. However, what attracts me most is the path made in the forest as voluntary work, which goes through some clearings and through several thickets; sometimes there you can dodge the branches that the snow bends over the path. I am in the forest, within its embrace. I don't ski fast on this slope, I ski slow. I look ahead, but I also stop to examine what I see on the ground beside the track. I will focus on the details. Sometimes I look up high. I'm taking my time. I concentrate on observing the trees, the inhabitants that make up the forest. I see familiar species from the northern forest: pines, birches and spruces, but each tree is an individual, its own species. The moss hanging from the branches of the trees means the air is clean. I take out my lungs full of fresh air, I enjoy it. I stare in awe at the old trees - ‘kelo’ in Finnish - dead, but still standing. I notice one tree with its branches wrapped around another tree; it is as if it is reaching out to protect the other. How little I still know about the way trees communicate with each other. The sunlight casts fascinating shadows on the tree trunks and the snow. For a moment, the snow sparkles like a diamond, dazzling my eyes. The tracks of the hare stand out amidst the snowdrifts. It jumps its own paths in this forest, our hidden treasure.